2016
DOI: 10.1002/2016ja022753
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial E region electric fields at the dip equator: 2. Seasonal variabilities and effects over Brazil due to the secular variation of the magnetic equator

Abstract: In this work, the seasonal dependency of the E region electric field (EEF) at the dip equator is examined. The eastward zonal (Ey) and the daytime vertical (Ez) electric fields are responsible for the overall phenomenology of the equatorial and low‐latitude ionosphere, including the equatorial electrojet (EEJ) and its plasma instability. The electric field components are studied based on long‐term backscatter radars soundings (348 days for both systems) collected during geomagnetic quiet days (Kp ≤ 3+), from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Resende et al () studied the competition between tidal winds and electric fields in the formation of Es b over SLZ. The authors reported an increase in the occurrence rates of Es b since 2009, revealing that the EEJ has little or no influence there, confirming the results of Tsunoda () about the anticorrelation characteristics between Es b and the EEJ intensity and Moro et al () about the secular variation of the geomagnetic field on the EEJ in terms of electric fields over SLZ.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Resende et al () studied the competition between tidal winds and electric fields in the formation of Es b over SLZ. The authors reported an increase in the occurrence rates of Es b since 2009, revealing that the EEJ has little or no influence there, confirming the results of Tsunoda () about the anticorrelation characteristics between Es b and the EEJ intensity and Moro et al () about the secular variation of the geomagnetic field on the EEJ in terms of electric fields over SLZ.…”
Section: Introductionsupporting
confidence: 68%
“…However, the electric field components presented an interesting dependence with the dip equator secular displacement effect at SLZ (see Figure 1 in Moro et al, 2016a), which causes different variations in E y and E z at JRO. This result led to a study on the seasonal dependence of E y and E z by Moro et al (2016b), which revealed for the first time the impact of the secular variation of the geomagnetic field on the EEJ in terms of electric fields.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our analysis, São Luís was still under the magnetic equator influence in 2005 and 2009, and thus two mechanisms can compete, neutral winds and electric fields, which are the responsible for the Es b layers formation or disruption. The secular variation on the geomagnetic field and its effect on the EEJ over Brazil is investigated by Moro et al (2016c).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there exists a gap in proper understanding the ionospheric variability in South America, especially in the Brazilian sector where there are some unique geophysical characteristics. One of them is the high magnetic declination angle that reaches approximately −20° in the equatorial region due to the dip equator secular displacement effect causing considerable changes in the Equatorial Electrojet and consequently in sporadic E (Es) layers (Denardini et al, ; Moro et al, , ; Moro et al, ; Resende et al, ). There is also a more pronounced energetic particle precipitation in the SAMA region (Moro et al, , ) when compared with other regions having the same latitudinal range, due to the global minimum in the intensity of the geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%